Rightlessness : Testimony and Redress in U.S. Prison Camps since World War II - Paik, A. Naomi (Book collections on Project MUSE., 2016)
In this work, A. Naomi Paik grapples with the history of US prison camps that have confined people outside the boundaries of legal and civil rights. In doing so, she reveals a powerful ongoing contest over the nature and meaning of the law, over civil liberties and global human rights, and over the power of the state in people's lives.